2005
DOI: 10.1007/s00421-004-1294-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on the fatty acid composition of lipid classes in rat liver, skeletal muscle, and adipose tissue

Abstract: The aim of the present study was to examine the effects of 8 weeks of exercise training on the fatty acid composition of phospholipids (PL) and triacylglycerols (TG) in rat liver, skeletal muscle (gastrocnemius medialis), and adipose tissue (epididymal and subcutaneous fat). For this purpose, the relevant tissues of 11 trained rats were compared to those of 14 untrained ones. Training caused several significant differences of large effect size in the concentrations and percentages of individual fatty acids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 33 publications
(45 reference statements)
5
44
1
Order By: Relevance
“…Because the serum leptin concentration is positively related to fat mass [22], our finding suggests a decrease in total body fat mass with training. Attesting to this are our previous findings of decreased triacylglycerol concentrations in the subcutaneous fat and gastrocnemius muscle of the same animals [21]. In addition, leptin's reduction can be considered as an adaptation to exercise training [13] because leptin has been reported to be lowered by exercise training in rats in an additive manner to body weight or body fat reduction [23][24][25].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Because the serum leptin concentration is positively related to fat mass [22], our finding suggests a decrease in total body fat mass with training. Attesting to this are our previous findings of decreased triacylglycerol concentrations in the subcutaneous fat and gastrocnemius muscle of the same animals [21]. In addition, leptin's reduction can be considered as an adaptation to exercise training [13] because leptin has been reported to be lowered by exercise training in rats in an additive manner to body weight or body fat reduction [23][24][25].…”
Section: Discussionmentioning
confidence: 80%
“…We have recently examined the effect of exercise training on the fatty acid composition of phospholipids and triacylglycerols in rat liver, skeletal muscle, and adipose tissue [21]. Along with several differences in the fatty acid profile of these tissues, we found lower triacylglycerol concentrations in skeletal muscle and subcutaneous fat of trained compared with untrained animals, as well as higher activities of 2 key enzymes of fatty acid oxidation, namely, carnitine palmitoyltransferase and 3-hydroxyacyl coenzyme A dehydrogenase in muscle.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the 'exercise' component of migration would likely have resulted in opposite changes from that observed in our study. Furthermore, the effect of exercise on muscle PL composition has been variable and inconsistent (Turner et al, 2004;Petridou et al, 2005). Helge and colleagues (Helge et al, 1999) found that the FA muscle membrane PL composition of trained rats was significantly different from that of sedentary rats fed the same diet (increased 18:2n-6, decreased 20:4n-6 and 22:6n-3).…”
Section: Seasonal Changes In Muscle Phospholipidsmentioning
confidence: 99%
“…It is known that the acceptability and quality of the products from Iberian pig are mainly attributed to differences in the fatty acid composition of adipose tissue. On the other hand, some experiments have reported a positive effect of exercise on human health due to that exercise may play an important role in several aspects of lipid metabolism such as lipolityc activity, oxidation, and elongation and desaturation of fatty acids (Petridou et al, 2005;Votruba et al, 2005;Bergouignan et al, 2006). To our knowledge there is not enough information on the possible effect of exercise on fatty acid composition of adipose tissue from Iberian pig reared indoor and fed mixed diets.…”
Section: Introductionmentioning
confidence: 97%